Navigating pedagogical translanguaging: Commentary on the special issue. (August 2020) - Byrnes, Heidi
Abstract: The special issue provides an outstanding opportunity for observing the situated nature of translanguaging theorizing itself and its attendant practices in diverse multilingual settings around the world. It does so by focusing on the construct of pedagogical translanguaging, particularly what we can learn from tension points that teachers might experience as they engage in acquiring knowledge and gain awareness about translanguaging, undertake complex decision-making that honors the particulars of their educational settings, initiate translanguaging practices, and refine these through repeated cycles of reflection and action in line with deeply held professional values and beliefs. I highlight larger lessons learned from the research presented in the collection's articles and the hopeful glimpses they offer for how we can arrive at and enact successful, because carefully situated, translingual practices.